Dual Polarization Single Port Inset Feed Microstrip Patch Array Antenna - Abd Aziz, M.Z.A.; Mohd Shah, M.S.R.; Suaidi, M.K.; Rahim, M.K.A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2011)
This paper present the designs of array antenna from type of inset-fed microstrip patch antenna by using single port oriented at 45° and -45°. The antennas are capable to generate dualpolarization radiation pattern centered at 45° and -45°. Combinations of two patches using quarter-wave impedance matching technique has been used to designs the array antennas operate at 2.4 GHz. The designs are simulated using Microwave Office 2004 and were fabricated on FR4 substrate with a dielectric constant εr =4.7, tan δ =0.019 and thickness =1.6mm. The simulation and measurement result have been compared. The 3 design 1x2 array antennas yield a bandwidth greater than 5%. The gain of the proposed antennas is also stable with operated frequency. The result showed that the combination of more patches in array can improve the return loss and gain performances.